Fighting against HIV and AIDS within a resource constrained rural setting: a case study of the Ruvheneko Programme in Chirumhanzu, Zimbabwe - Christina Tafadzwa Dzimiri; Patrick Dzimiri; Kezia Batisai (Taylor & Francis Group, 2019)
Since reports of the first incidence of the HIV virus in Zimbabwe in 1985, the epidemic has negatively impacted on every facet of human security. Rural areas, by virtue of being the periphery and constrained in terms of resources and health care provision, bear the brunt of the epidemic. In light of the above background, this paper examined how the establishment of Ruvheneko Programme by the people of Chirumhanzu helped in mitigating on the impact of HIV and AIDS in the rural sphere. The paper analyses how the community of Chirumhanzu successfully engaged each other to the extent of coming up with such a vibrant programme. This is raised against the backdrop of failure usually associated with HIV and AIDS engagement projects. The study made use of field interviews and focus group discussions as data collection instruments. Participants were purposively selected on the basis of their knowledge and participation in the establishment and activities of Ruvheneko Programme. Selected were 5 St Theresa's Hospital Staff, 10 Roman Catholic Church members of which, 5 were from the St Anna's woman prayer group and 5 men from St Joseph's men prayer group, 1 village head and 2 elders from the same nearby village constituted key informants. Complementing the use of interviews and focus group discussions was the analysis of secondary data sources on HIV and AIDS in Zimbabwe as well as the Ruvheneko Programme. To understand the collective role of various sectors of the community in establishing Ruvheneko Programme, the paper derives insights from the perspective of social capital theory and its notion of commonality to strengthen communities. Findings from the study show that, unlike other HIV and AIDS programmes that are exported from the urban to the rural areas, Ruvheneko Programme demonstrates a grassroots-level response to HIV and AIDS. Again, social cohesion fostered by aspects such as religiosity, cultural ethos of Ubuntu, and a consultative approach played a key role in unifying people towards fighting HIV and AIDS in Rural Chirumhanzu.